Spatiotemporal Variations of Freezing and Thawing Indices During the Past Four Decades in Tibet - Liao, Ying; Li, Yiying; Fan, Jihui; Galoie, Majid; Motamedi, Artemis (Frontiers in Ecology and Evolution, 2021)
Freezing and thawing indices (FI and TI) are commonly used as indicators for climate change assessment and permafrost extent estimation in cold regions. In this study, based on the meteorological daily data (1978–2017) among 34 meteorological stations in Tibet, the temperature in space has been interpolated and FI and TI have been calculated. Finally, spatiotemporal variations have been analyzed and the permafrost area has been estimated. The results showed the mean annual of FI and TI in Tibet are 1241.36 and 1290.22°C⋅day, respectively. A significant downward trend in freezing index (FI) and an upward trend in thawing index (TI) have been reported in the time series, in against, analyzing the spatial distribution showed there is an increasing trend from southeast to northwest for FI while TI was decreased gradually in the same region in Tibet. This research indicates that altitude has a significant influence on the change of FI and TI. With the increase of altitude, FI decreased and TI increased more significantly. The permafrost area was estimated at about 0.59 × 106 km2 in Tibet.